Two new species and a key to nine species of the genus Mongolotettix Rehn, 1928 from China (Acrididae, Acridoidea, Orthoptera) - Shi, Jian-Ping; Liu, Zhi-Wei; Li, Bao-Ping (Zootaxa, 2016)
Two new species of the genus Mongolotettix Rehn, 1928 from China, i.e. Mongolotettix wulingyuanensis sp. nov. and Mongolotettix. shaanxiensis sp. nov. are described herein. M. wulingyuanensis sp. nov. is similar to M. angustiseptus Wan, Ren & Zhang, 1998, but differs from the latter by body larger, length of body ♂ 25.6 mm, ♀ 39.1mm; tegmina of male without a white stripe on the fore margin at base; subgenital plate of male conical, sides concave, apex acute; both outer sides of epiphallus without acute projection in the middle. M. shaanxiensis sp. nov. is similar to M. anomopterus (Caudell, 1921), but differs from the latter by tegmina of male longer, reaching the end of epiproct, without a white stripe on the fore margin at base, tegmina of female longer, reaching the middle of 2nd abdominal tergum, width of epiphallus larger than height, upper ovipositor valve slender, length 3.8 times its maximum width. A key to all nine known species of the genus from China is given. Type specimens are deposited in the Northwest Plateau Institute of Biology, Chinese Academy of Sciences, Xining, 810001, China.